Impacts of the COVID-19 Pandemic on Family Mental Health in Canada: Findings from a Multi-Round Cross-Sectional Study - Kimberly C. Thomson (MDPI AG, 2021)
Pandemic-related disruptions, including school, child care, and workplace closures, financial stressors, and relationship challenges, present unique risks to families’ mental health. We examined the mental health impacts of the coronavirus disease 2019 (COVID-19) pandemic among parents with children <18 years old living at home over three study rounds in May 2020 (n = 618), September 2020 (n = 804), and January 2021 (n = 602). Data were collected using a cross-sectional online survey of adults living in Canada, nationally representative by age, gender, household income, and region. Chi-square tests and logistic regression compared outcomes between parents and the rest of the sample, among parent subgroups, and over time. Parents reported worsened mental health compared with before the pandemic, as well as not coping well, increased alcohol use, increased suicidal thoughts/feelings, worsened mental health among their children, and increases in both negative and positive parent–child interactions. Mental health challenges were more frequently reported among parents with pre-existing mental health conditions, disabilities, and financial/relationship stressors. Increased alcohol use was more frequently reported among younger parents and men. Sustained mental health challenges of parents throughout nearly a year of the pandemic suggest that intervention efforts to support family mental health may not be adequately meeting families’ needs. Addressing family stressors through financial benefit programs and virtual mental health supports should be further explored.